The Effect Of Competitive Advantage And Market Orientation On Marketing Performance in Chicken Business In Medan - Rahmad Hudapi Purba; M. Isa Indrawan; Ramadhan (Britain International for Academic Research (BIAR) Publisher, 2022)
This study aims to determine whether competitive advantage and market orientation simultaneouslypositive and significant effecttomarketing performance beef chicken business in Medan, Jalan Sei Sikambing, Jalan Kampung Lalang and Jalan Petisah. The data analysis technique used is the quantitative associative method with the help of the SPSS program. This study uses multiple linear regression analysis. The research sample was 96 respondents. Primary data collection using a questionnaire. The results show that competitive advantage and market orientation simultaneouslypositive and significant effecttomarketing performance beef chicken business in Medan, Jalan Sei Sikambing, Jalan Kampung Lalang and Jalan Petisah.